Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

With $\mathbf{u,v}$ being vectors in $\mathbb{R}^n$ euclidean space, the Cauchy–Schwarz inequality is

$$ {\left(\sum_{i=1}^{n} u_i v_i\right)}^2 \leq \left(\sum_{i=1}^{n} u_i^2\right)\left(\sum_{i=1}^{n} v_i^2\right) $$

further given that $\mathbf{u}=\lambda\mathbf{v}$, the csi looks like the following:

$$ {\left(\sum_{i=1}^{n} \lambda v_i v_i\right)}^2 \leq \left(\sum_{i=1}^{n} (\lambda v_i)^2\right)\left(\sum_{i=1}^{n} v_i^2\right) $$

With equality applying in the Cauchy-Schwarz inequality only if $\mathbf{u,v}$ are linear dependent, how do I show that equality is given in this case? A start would be enough, I'm quite new to linear algebra

Thanks so far!
Rewriting the last line - following your advice - I get the following

$$ {\lambda^2\left(\sum_{i=1}^{n} v_i^2\right)}^2 \leq \lambda^2\sum_{i=1}^{n} v_i^2\sum_{i=1}^{n} v_i^2 $$

Okay I'm not sure about the following, so make sure you have foul fruit nearby to throw at me:

Canceling $\lambda^2$ this results in

$$ {\left(\sum_{i=1}^{n} v_i^2\right)}^2 \leq \sum_{i=1}^{n} v_i^2\sum_{i=1}^{n} v_i^2 $$

with the inquality being wrong, equality applies... is that evidence enough?

share|cite|improve this question
check :… – MSEoris May 8 '13 at 12:14
Re-write the left hand side as the product of two summations and factor out the constant from both sides and it should become a lot clearer to you that way. – BU982T May 8 '13 at 12:15
up vote 2 down vote accepted


$$\left(\sum_{i=1}^n\lambda v_iv_i\right)^2=\lambda^2\left(\sum_{i=1}^n v_i^2\right)^2$$

$$\sum_{i=1}^n (\lambda v_i)^2\sum_{j=1}^n (v_j)^2=\lambda^2\sum_{i=1}^n v_i^2\sum_{j=1}^n v_j^2$$

share|cite|improve this answer
I've updated my question with what I think might be the solution, would you mind taking a look at it? – Rickyfox May 8 '13 at 13:12
Yes...and that's an equality. For example, for $\,n=3\,$ :$$(x^2+y^2+z^2)^2=(x^2+y^2+z^2)(x^2+y^2+z^2)$$...:) ! – DonAntonio May 8 '13 at 14:40

Expand the following expression to get a trinom in $\lambda$:

$$\sum_{i=1}^n \left(u_i - \lambda v_i\right)^2$$

Then, write that since it's positive or zero for all values of $\lambda$, the discriminant of the trinom is negative or zero. This will give you Cauchy-Schwarz inequality. Now, equality case is found when the discriminant is zero, that is, when there is some $\lambda$ such that the first expression is zero, which gives an obvious condition between $u_i$ and $v_i$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.